Fleas - Hoke, Helen, 1903-; Pitt, Valerie (New York, Watts, 1974)
Describes the anatomy and habits of fleas and how the diseases they carry have, in some cases, altered history.
Bibliography: p. 85-86.
Keywords: Fleas -- Juvenile literature; Fleas